2023
DOI: 10.3390/ijms242317010
|View full text |Cite
|
Sign up to set email alerts
|

Col1A-2 Mutation in Osteogenesis Imperfecta Mice Contributes to Long Bone Fragility by Modifying Cell-Matrix Organization

Grégoire André,
Antoine Chretien,
Antoine Demoulin
et al.

Abstract: Osteogenesis imperfecta (OI) is a rare congenital bone dysplasia generally caused by a mutation of one of the type I collagen genes and characterized by low bone mass, numerous fractures, and bone deformities. The collagen organization and osteocyte lacuna arrangement were investigated in the long bones of 17-week-old wildtype (WT, n = 17) and osteogenesis imperfecta mice (OIM, n = 16) that is a validated model of severe human OI in order to assess their possible role in bone fragility. Fractures were counted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…According to Agustiana et al (2023), the protein concentration from A. chacunda has the best base material of ash and carbohydrate content. A drawback of this fish is its numerous bones (André et al 2023), which are similar to those found in the fish Puput (Ilisha elongata) (Liu et al 2022), where I. elongata and A. chacunda have something in common, namely numerous bones and a flat shape (Firdaus and Salim 2011). The ecological habitat of A. chacunda is located in coastal waters (Amran and Daming 2023) and estuaries (Salim et al 2022), with a substantial population feeding primarily on benthic organisms (Barrera-Oro et al 2019) and Bacillariophyceae (Wang et al 2022) detritus (Liu and Yao 2023), thus this species categorized as omnivores and pelagic feeders (Hein et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…According to Agustiana et al (2023), the protein concentration from A. chacunda has the best base material of ash and carbohydrate content. A drawback of this fish is its numerous bones (André et al 2023), which are similar to those found in the fish Puput (Ilisha elongata) (Liu et al 2022), where I. elongata and A. chacunda have something in common, namely numerous bones and a flat shape (Firdaus and Salim 2011). The ecological habitat of A. chacunda is located in coastal waters (Amran and Daming 2023) and estuaries (Salim et al 2022), with a substantial population feeding primarily on benthic organisms (Barrera-Oro et al 2019) and Bacillariophyceae (Wang et al 2022) detritus (Liu and Yao 2023), thus this species categorized as omnivores and pelagic feeders (Hein et al 2018).…”
Section: Introductionmentioning
confidence: 99%